2017
DOI: 10.12659/msm.902859
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol Promotes Vascular Endothelial Growth Factor (VEGF)-Mediated Diabetic Wound Healing in Streptozotocin-Induced Hyperglycemic Rats

Abstract: BackgroundWound healing in chronic diabetic mellitus is mainly associated with the management of angiogenesis. The angiogenic mechanism of vascular endothelial growth factor (VEGF) has been widely studied in the context of diabetic ulcers. The aim of this study was to investigate the wound-healing potential of curcumol in streptozotocin-induced diabetic rats.Material/MethodsSixty male SD (Sprague Dawley) rats were purchased and randomly assigned into four groups: a control group and a model group treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…In addition, studies investigated the effect of curcumol in suppressing TGF- β 1 led to the decrease of epithelial-mesenchymal transition occurrence. Reports also show that curcumol may modulate inflammatory and enhanced angiogenesis, resulting in better wound healing [2830]. Our findings demonstrated that curcumol and curcumin could inhibit the TGF- β 1/Smads signaling pathway too by reducing the mRNA expression levels of fibrotic factors α -SMA, Smad2/3 and TGF- β .…”
Section: Discussionsupporting
confidence: 66%
“…In addition, studies investigated the effect of curcumol in suppressing TGF- β 1 led to the decrease of epithelial-mesenchymal transition occurrence. Reports also show that curcumol may modulate inflammatory and enhanced angiogenesis, resulting in better wound healing [2830]. Our findings demonstrated that curcumol and curcumin could inhibit the TGF- β 1/Smads signaling pathway too by reducing the mRNA expression levels of fibrotic factors α -SMA, Smad2/3 and TGF- β .…”
Section: Discussionsupporting
confidence: 66%
“…In this study, VCN-2 accelerated diabetic wound healing through the VEGF signalling pathways. Similarly, Zhou et al [63] revealed that the angiogenesis of diabetic rat skin ulcers was accelerated by curcumol via VEGF pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Curcumol has been isolated from C. longa which is an imperative species of the genus Curcuma and is generally known as common turmeric. Curcumol was also extracted from the rhizome of C. aeruginosae that is effective for antiinflammatory and antioxidant activities [20]. C. aromatic, a well-known natural source of curcumol, has been reported for its antitumor and antimicrobial activities [21].…”
Section: Curcumol and Its Natural Sourcesmentioning
confidence: 99%
“…The summary of plants containing curcumol and biological activities are enlisted in Table 1. Figure 1 provides natural sources of curcumol including Astragali radix [36], C. aeruginosae [20], C. aromatica [21], C. kwangsiensis [22], C. longa [37], C. phaeocaulis [24], C. wenyujin [38], C. zedoary [28], Fructus gardenia [35], and C. trichosantha G. [39].…”
Section: Curcumol and Its Natural Sourcesmentioning
confidence: 99%